Factors Contributing to Undergraduate Students’ Satisfaction and Continuance Intention of the Chaoxing Learning Platform in Yibin, China - Tao, Yuezhen (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study identified key factors influencing undergraduate students’ satisfaction and continuance intention to use the Chaoxing Learning Platform in Yibin, China. The conceptual framework illustrated the cause-and-effect relationships between System Quality (SQ), Information Quality (IQ), Perceived Usefulness (PU), Confirmation (COF), Subjective Norm (SN), Satisfaction (SAT), and Continuance Intention (CI). Research design, data and methodology: The researcher employed a quantitative approach (n=500) to distribute questionnaires to undergraduate students from the School of Mechanical Engineering at Sichuan University of Science & Engineering in Yibin, Sichuan Province, China. The study utilized non-probability sampling techniques, including judgmental sampling to select four target grades, quota sampling to determine the sample size, and convenience sampling for data collection and online questionnaire distribution. Data analysis was performed using structural equation modeling (SEM) and confirmatory factor analysis (CFA) to assess model fit, reliability, and construct validity. Results: The results indicated that System Quality, Information Quality, Perceived Usefulness, and Confirmation significantly impacted Satisfaction. Additionally, Satisfaction and Subjective Norm significantly influenced Continuance Intention. Conclusions: It is recommended that university administrators and platform developers focus on improving factors such as system quality, information quality, and perceived usefulness. Additionally, promoting social influence through instructor and peer engagement can enhance student satisfaction and encourage the long-term use of the Chaoxing Learning Platform.